PENDEKATAN EKSPLORASI MENGENAI PERSEPSI MASYARAKAT DALAM MENGGUNAKAN E-MONEY PADA JALUR TOL DI KOTA MAKASSAR - Hendrikus Kadang; Virginia Rosalia G; Thomas Th. Abraham; Nataniel Papalangi (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2020)
Various studies on the use of e-money have been conducted and most of them use the positivism approach, so that it is rarely found in the form of an exploration approach especially with regard to toll roads. The purpose of this study is to explore, describe and analyze people's perceptions in using e-money on the toll road in Makassar City. This study uses a semi-structured interview method in the process of collecting data in the analysis unit. The population of this study consists of three categories: toll road users and e-money users, e-money experts, and toll service providers with 10 participants to be interviewed. Data analysis method used is thematic analysis with the help of cross-case analysis. Based on the results of open coding, it can be concluded that e-money is one form of easy transactions and the use of e-money that is safe, efficient payment and saves time, e-money risk levels are lower. Meanwhile, the way to overcome the problem of using e-money on toll roads is to print and save transaction receipts, maintain e-money cards, make compensation, prepare officers, socialize, and register with vendors.